HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA JURUSAN SEJARAH FAKULTAS ILMU BUDAYA UNIVERSITAS DIPONEGORO - Salsabila, Wina Klarissa; Indrawati, Endang Sri (Jurnal EMPATI, 2019)
are carried out in a repetitive and willful manner. Emotional intelligence is the ability to recognize and manage emotions that arise so that individuals put the emotions appropriately according to the situation in the environment. This study aims to determine whether there is a relationship between emotional intelligence with academic procrastination on the thesis of Historical Science Department student at the Faculty of Cultural Sciences, Diponegoro University. The population in this study is 108 students with research subjects 60 students using convenience sampling techniques.Â  This research using the Academic Procrastination Scale (30 items, Î± = 0.913) and the scale Emotional Intelligence (24 items, Î± = 0.896). This research uses analysis simple regression and indicate that there is a significant negative relationship between emotional intelligence and academic procrastination (r xy = -0,381 p = 0.001). The higher the emotional intelligence, the lower Student academic procrastination, on the contrary the lower the emotional intelligence, the higher the academic procrastination of students. Intelligence emotional contribute 14.5% to procrastination academic.Â Keywords: emotional intelligence, academic procrastination, studentsÂ